MENGURANGI RESIKO KEKAMBUHAN HIPERTENSI MELALUI PENYULUHAN KESEHATAN DAN PENATALAKSANAAN NONFARMAOLOGI PADA LANSIA - Andri Kusuma Wijaya; Fatsiwi Nunik Andari; Emi Kosvianti (Gayaku Publisher, 2024)
Hypertension or what can be simplified is called high blood pressure at a level of 140 mmHg or more and diastolic blood pressure at a level of 90 mmHg or more. Hypertension can attack almost all groups of people throughout the world, where the number of people who suffer from hypertension always increases from year to year, including the elderly. Elderly is a stage where the continuation of the human life process is characterized by a process of decreasing function of the body's ability to deal with changes in stressful conditions due to the surrounding environment. This aging process is a form of decline in the role of the anatomical function of the human body, where this condition is actually a biological phenomenon that can be comprehensive with signs of ongoing evolution and maturation of the organism. One of the changes occurs in the vascular system where the blood vessels thicken in the child, thus triggering hypertension. Hypertension can be prevented or controlled through efforts starting from health check-up activities such as measuring blood pressure, providing health education about hypertension, a healthy diet that is low in salt, fat or cholesterol and consuming foods high in fiber and regularly doing exercise such as hypertension exercises so that it can controlling blood pressure in the elderly. Therefore, it is considered necessary for elderly people to undergo a health check and then be given health education about hypertension, a low salt, low cholesterol diet, high fiber foods and regular exercise for hypertension so that it is hoped that elderly people who experience hypertension can control the increase in blood pressure that occurs in these elderly people.